2019
DOI: 10.1038/s41593-019-0556-3
|View full text |Cite|
|
Sign up to set email alerts
|

Dopamine metabolism by a monoamine oxidase mitochondrial shuttle activates the electron transport chain

Abstract: Monoamine oxidase (MAO) metabolizes cytosolic dopamine (DA) thereby limiting autooxidation, but is also thought to generate cytosolic hydrogen peroxide (H 2 O 2 ). We show that MAO metabolism of DA does not increase cytosolic H 2 O 2 , but leads to mitochondrial electron transport chain (ETC) activity. This was dependent upon MAO anchoring to the outer mitochondrial membrance and shuttling of electrons through the intermembrane space to support the bioenergetic demands of phasic DA release.Monoamine oxidases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 27 publications
4
121
0
Order By: Relevance
“…The cyclization of dopamine quinones forms aminochrome, which generates superoxide and down-regulates antioxidative nicotinamide adenine dinucleotide phosphate (NADPH) [ 8 ]. The metabolism of DA by monoamine oxidase-B (MAO-B) generates 3,4-dihydroxyphenyl-acetaldehyde, ammonia and H 2 O 2 [ 9 ]. H 2 O 2 in DAergic neurons reacts with Fe 2+ to form hydroxyl radical [ 10 , 11 ].…”
Section: Ros Production In the Pd Brainmentioning
confidence: 99%
“…The cyclization of dopamine quinones forms aminochrome, which generates superoxide and down-regulates antioxidative nicotinamide adenine dinucleotide phosphate (NADPH) [ 8 ]. The metabolism of DA by monoamine oxidase-B (MAO-B) generates 3,4-dihydroxyphenyl-acetaldehyde, ammonia and H 2 O 2 [ 9 ]. H 2 O 2 in DAergic neurons reacts with Fe 2+ to form hydroxyl radical [ 10 , 11 ].…”
Section: Ros Production In the Pd Brainmentioning
confidence: 99%
“…Interestingly, a recent paper has confirmed in hippocampal neurons that Ca 2+ influx through Cav1 channels combined with CICR can regulate mitochondria ATP production, although in these non-pacemaking neurons mitochondrial contribution to cell bioenergetic seems to be relatively small and this mechanism is activated only upon stimulation [ 163 ]. At axonal DA release sites, Ca 2+ stimulated mitochondrial OXPHOS is complemented by another feedforward system in which DA transiting the cytosol is metabolized by monoamine oxidase (MAO) anchored to the outer membrane of mitochondria; in so doing, MAO generates an electron that is shuttled to the ETC, which supports the electrochemical gradient used by complex V to generate ATP [ 164 ]. Thus, feedforward control of mitochondrial OXPHOS is a mechanism by which SN DAergic neurons can maximize their functionality and promote organismal survival.…”
Section: Ca 2+ Signaling In Sn Daergic Neuronsmentioning
confidence: 99%
“…Numerous studies have reported the successful application of genetically encoded biosensors that are sensitive to a variety of metabolites and signaling molecules, including ions and neurotransmitters, to investigate the functioning of neurons and glia in in vitro systems under diverse physiological (spontaneous and evoked activity of neuronal and glial cells) or pathological (Parkinson’s disease, Rett syndrome, and spinal muscular atrophy) conditions. Genetically encoded biosensors were applied to visualize the release of neurotransmitters and their intracellular dynamics [ 260 , 261 , 262 ], to observe the metabolic activity (glucose, pyruvate, ATP) and functioning of second messenger systems (Ca 2+ , cAMP) [ 263 , 264 , 265 , 266 ], to detect the formation of ROS [ 267 , 268 , 269 , 270 ], and to record the responses of cellular redox systems [ 183 , 271 , 272 , 273 , 274 , 275 ]. However, many fewer studies have attempted to exploit genetically encoded sensors for the real-time evaluation of alterations in cell signaling and metabolism in in vitro models of brain hypoxic injury.…”
Section: In Vitro Models For Real-time Imaging Of Cell Signaling Amentioning
confidence: 99%